Sur/South : poetics and politics of thinking Latin America / India - Klengel, Susanne; Ortiz Wallner, Alexandra (Bibliotheca Ibero-Americana ;, 2016)
"An awareness of the cultural entanglements in the Global South has become an evident as well as urgent factor in the global constitution of knowledge and the knowledges of globalization. This book contributes to the growing field of research on the relations between Latin America and Asia. From multiple perspectives and disciplinary backgrounds, it addresses the cultural and intellectual entanglements between Latin America and India in the 20th century. The Sur / South cultural cartography that emerges reveals the need for a new reflection on Orientalism as well."--P. [4] of cover.